On forms of address in present-day Peru. An analysis of And suddenly an angel, by Jaime Bayly - Arrizabalaga Lizarraga, Carlos (2020)
The expression of politeness in languages is closely linked to changes in social life. This paper aims to investigatethe forms of address used in present-day Peru on the assumption that they imply a certain correlation with the changes happened in the Peruvian society in recent decades, since they are a clear expression of the social structure (Escandell, 2013, p. 144). This paper takes as an object of analysis a recent novel that shows the relationship of inequality between a maid and her employer as well as, it shows the reflection of social differences in the use of forms of address between them, and among the other characters in the novel by Jaime Bayly (Lima, 1965). The disappearance of forms such as niño, patrón, patroncito (child, master,boss) and the introduction of the term joven (young man) in complementary opposition to señor (sir) is manifested.